Solid Fuels Combustion and Gasification. Modeling, Simulation, an Equepment Operation - SOUZA-SANTOS, Marcio L De (Marcel Dekker, 2004)
Solid Fuels Combustion and Gasification. Modeling, Simulation, and Equipment ...